Local compactness in approach spaces I - R. Lowen; C. Verbeeck (International Journal of Mathematics and Mathematical Sciences)
This paper introduces some definitions of a concept of local compactness in approach spaces. The basic relationships between these concepts is studied, and measures of local compactness are defined.